Cytotoxicity and DNA damage in the neutrophils of patients with sickle cell anaemia treated with hydroxyurea (Brazilian Journal of Pharmaceutical Sciences, 2014)
Hydroxyurea (HU) is the most important advance in the treatment of sickle cell anaemia (SCA) for preventing complications and improving quality of life for patients. However, some aspects of treatment with HU remain unclear, including their effect on and potential toxicity to other blood cells such as neutrophils. This study used the measurement of Lactate Dehydrogenase (LDH) and Methyl ThiazolTetrazolium (MTT) and the comet assay to investigate the cytotoxicity and damage index (DI) of the DNA in the neutrophils of patients with SCA using HU.In the LDH and MTT assays, a cytoprotective effect was observed in the group of patients treated, as well as an absence of toxicity. When compared to patients without the treatment, the SS group (n=20, 13 women and 07 men, aged 18-69 years), and the group of healthy individuals (AA) used as a control group (n=52, 28 women and 24 men, aged 19-60 years), The SSHU group (n=21, 11 women and 10 men, aged 19-63 years) showed a significant reduction (p